Total transmission and super reflection realized by anisotropic zero-index materials - Hui Feng Ma; Jin Hui Shi; Ben Geng Cai; Tie Jun Cui (New Journal of Physics, 2012)
We demonstrate theoretically and experimentally total transmission and super reflection which are realized by anisotropic zero-index materials (AZIMs). We show that total transmission will be observed when using a rectangular perfectly magnetic conductor (PMC)-coated object sandwiched by two AZIM slabs, which has the properties of μ _rx  = 0 (in the normal direction to the wavefronts) and μ _ry  =  ε _rz  = 1 for transverse-electric polarized incident waves. When the object is coated with a perfectly electric conductor (PEC), however, the incident waves will be totally reflected by the finite-sized object in the way of an infinite PEC plane, generating a super reflection. Closed-form formulas are derived to explain the physical mechanisms of total transmission and super reflection, which agree with the full-wave numerical simulations perfectly. Experimental samples of AZIM and PMC are designed, fabricated and measured in the microwave frequency, which show good transparent and super-reflecting effects.